2021
DOI: 10.1001/jamanetworkopen.2021.36150
|View full text |Cite
|
Sign up to set email alerts
|

Morally Injurious Experiences and Emotions of Health Care Professionals During the COVID-19 Pandemic Before Vaccine Availability

Abstract: Key Points Question How did health care workers experience moral injury during the COVID-19 pandemic before the availability of vaccines? Findings In this qualitative study of 1344 health care professionals in 2020, respondents reported significant changes in their personal and professional lives during the course of the pandemic. Common themes were feeling isolated from non–health care professionals, alienated from patients, and betrayed by coworkers, admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 28 publications
(73 reference statements)
1
36
0
Order By: Relevance
“…These sources of moral distress continued to be present during Surveys 2 and 3, despite the fact that those surveys were deployed at a time when some social restrictions had been lifted and progress was being made in the provincial vaccination program. This finding highlights the constant pressure that BC HCWs experienced during at least the first 15 months of the BC pandemic response and contrasts with that of Song [ 27 ]. In their study, which also included several surveys deployed at different times during the COVID-19 pandemic, the authors found that by stage 2 (24 October to 30 November 2020) the participants expressed “ resignation around adapting to the new normal ” [ 26 ] (p. 3).…”
Section: Discussionmentioning
confidence: 94%
“…These sources of moral distress continued to be present during Surveys 2 and 3, despite the fact that those surveys were deployed at a time when some social restrictions had been lifted and progress was being made in the provincial vaccination program. This finding highlights the constant pressure that BC HCWs experienced during at least the first 15 months of the BC pandemic response and contrasts with that of Song [ 27 ]. In their study, which also included several surveys deployed at different times during the COVID-19 pandemic, the authors found that by stage 2 (24 October to 30 November 2020) the participants expressed “ resignation around adapting to the new normal ” [ 26 ] (p. 3).…”
Section: Discussionmentioning
confidence: 94%
“…In sum, groups are involved with shaping moral norms and appraising events. It is no wonder that a common indication of moral injury is social detachment and isolation 3 14 33. When people perceive themselves as having violated group norms, fear of social rejection is commonly experienced as shame.…”
Section: The Social-contextual Nature Of Moral Injurymentioning
confidence: 99%
“…Fear and uncertainty about the transmissibility of a novel virus was compounded by limited resources (eg, personal protective equipment (PPE), ventilators, extracorporeal membrane oxygenation, dialysis, staffing) which gave rise to tragic dilemmas in which not all patients could be treated according to ordinary standards of care, resulting in death for some patients 38–41. While the disease arose from a virus, systems and human agency were ingredient to the emergence of moral injury (eg, limited stock piles of PPE as a cost-saving measure, inadequate administrative response) and, more broadly, to the marked racial and socioeconomic disparities in COVID-related morbidity and mortality 14 42. In later stages of the pandemic, patterns of behaviour (eg, vaccine refusal which strained medical systems) contributed to conditions which limited the ability of healthcare professionals to care for patients.…”
Section: The Social-contextual Nature Of Moral Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Health and frontline workers were the most exposed to the development of the fear of COVID-19 [ 3 , 4 , 5 , 6 , 7 ], even with respect to their own family members contracting the virus [ 8 , 9 ]. Most of the literature [ 10 , 11 , 12 , 13 , 14 , 15 ] has investigated mental health in health care workers; however, only a few studies [ 16 , 17 , 18 ] have investigated the effects of the pandemic on the psychological health of humanitarian volunteers who play an important role in the management of emergencies. In fact, during the COVID-19 pandemic, as well as in past epidemics [ 19 ], the overload of intensive care units for the management of the critically ill has challenged national health systems.…”
Section: Introductionmentioning
confidence: 99%